On the problem of determining the parameter of an elliptic equation in a Banach space - Ashyralyev, Allaberen; Ashyralyyev, Charyyar (Nonlinear Analysis: Modelling and Control, 2014)
The boundary value problem of determining the parameter of an elliptic equation -u''(t)+Au(t)=f(t)+p (0⩽t⩽T), u(0)=φ, u(T)=ψ, u(λ)=ξ, 0
Keywords: elliptic equations; boundary value problems; positivity; exact estimates; stability